Fundamental Differences in Inactivation Mechanisms of Escherichia coli O157:H7 Between Chlorine Dioxide and Sodium Hypochlorite - Bridges, David F.; Lacombe, Alison; Wu, Vivian C. H. (Frontiers in Microbiology, 2022)
Chlorine dioxide (ClO2) and sodium hypochlorite (NaClO) are two chlorinated oxidizing agents that are implemented in water treatment and postharvest processing of fresh produce. While the antibacterial mechanisms of NaClO have been investigated, there are comparatively few studies that have looked at how ClO2 kills bacteria. Therefore, the objective of this study was to compare the inactivation pathways of ClO2 and NaClO against Escherichia coli O157:H7. Treatments consisted of 2.5, 5, and 10 ppm ClO2 or 50, 100, and 200 ppm NaClO for 5, 10, and 15 min. Maximum log reductions of E. coli O157:H7 were 5.5 and 5.1 after treatment with ClO2 or NaClO, respectively. Bacterial inactivation was measured using log reductions, intracellular reactive oxygen species (ROS) using with 2’,7’–dichlorofluorescin diacetate (DCFDA) or aminophenyl fluorescein (APF) probes, relative values of NAD+, NADH, NADP+, and NADPH cofactors. Additionally, the expression of three key genes involved in ROS stress was measured via RT-PCR. Levels of intracellular ROS measured by DCFDA after ClO2 treatment were significantly higher than those found after treatment in NaClO. Additionally, NaClO treatment resulted in upregulation of ROS-defense genes, while expression of the same genes was typically at base levels or downregulated after ClO2 treatment. As the concentrations of both treatments increased, the NADP+:NADPH ratio shifted to the cofactor being predominantly present as NADP+. These data indicate that ClO2 and NaClO damage E. coli O157:H7 via measurably different mechanisms and that ClO2 does not appear to cause substantial oxidative stress to E. coli O157:H7 directly.